Challenges with Evaluating Education Policy Using Panel Data during and after the COVID-19 Pandemic. Issue 3 (3rd July 2021) - Feller, Avi; Stuart, Elizabeth A.
Abstract: Panel data methods, which include difference-in-differences and comparative interrupted time series, have become increasingly common in education policy research. The key idea is to use variation across time and space (e.g., school districts) to estimate the effects of policy or programmatic changes that happen in some localities but not others. In this commentary we highlight some specific challenges for panel or longitudinal studies of K-12 education interventions during and following the COVID-19 pandemic. Our goal is to help researchers think through the underlying issues and assumptions, and to help consumers of those studies assess their validity.